2020
DOI: 10.1021/acs.cgd.0c00411
|View full text |Cite
|
Sign up to set email alerts
|

Urea-Based Macrocycle Selective for Sulfate and Structurally Sensitive to Water

Abstract: An unsymmetrical semirigid tetraurea macrocycle, 1, selectively traps SO 42− with high affinity in a 0.5% water:DMSO-d 6 solution (K a = 90,500 M −1 ). The macrocycle displays somewhat less affinity for HSO 4 − (K a = 68,600 M −1 ), while K a 's for OAc − and H 2 PO 4− are approximately half that seen for SO 4 2− (49,800 and 52,600 M −1 , respectively). Cl − binds weakly (K a = 3430 M −1 ), and essentially no affinity is observed for NO 3 − . Structural results for the SO 4 2− and Cl − complexes indicate 1:1 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…6,7 Over the past few decades, plentiful receptors have been intentionally made and demonstrated to bind sulfate anions with high affinity and selectivity. [8][9][10][11] The receptors are typically programmed with hydrogen-bonding donors or/and electrostatic moieties to stabilize sulfate anions, e.g., urea unit, 12,13 guanidium, 14,15 imidazolium, 16 and aryl-triazoles. 17 In con-trast, sulfate separation from water remains a great challenge on account of the large free energies of sulfate hydration (−1080 kJ mol −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Over the past few decades, plentiful receptors have been intentionally made and demonstrated to bind sulfate anions with high affinity and selectivity. [8][9][10][11] The receptors are typically programmed with hydrogen-bonding donors or/and electrostatic moieties to stabilize sulfate anions, e.g., urea unit, 12,13 guanidium, 14,15 imidazolium, 16 and aryl-triazoles. 17 In con-trast, sulfate separation from water remains a great challenge on account of the large free energies of sulfate hydration (−1080 kJ mol −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…5), which demonstrated nearly the same chemical shift changes as observed for F À alone, supporting a strong selectivity of macrocycle 1 for the F À ion. 34 Considering a structural similarity between the isophthalamide and pyridine-2,6-diamide moieties, we next studied the anion binding properties of macrocycle 2 containing the isophthalamide linkage. Interestingly, this macrocycle exhibited an approximately 2-fold improvement in the affinity for AcO À , PhCOO À , and H 2 PO 4 À (also forming the 1 : 1 complex in these cases, see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5), which demonstrated nearly the same chemical shift changes as observed for F − alone, supporting a strong selectivity of macrocycle 1 for the F − ion. 34…”
Section: Resultsmentioning
confidence: 99%
“…1 Through elegant molecular designs and synthetic methodologies, 2,3 various macrocyclic structures have been made and engineered with specific monomer sequences for the uses of molecular recognition, [4][5][6] chemical storage and separation, 7,8 catalysis, [9][10][11] molecular machines, 12 assemblies, [13][14][15][16] and adaptive materials. [17][18][19] Benefitting from the characteristic hydrogen bonding nature (high-rigidity and self-complementarity) of the urea unit, 20,21 urea-based macrocycles have attracted great attention in the studies of anion recognition [22][23][24][25][26] and hierarchical assembly. [27][28][29] However, compared to the well-established industrialization of polyurea elastomer materials, 30 the oligourea macrocycles are far less explored because the intermolecular hydrogen bonding of urea units may induce poor solubility of the desired macrocycles thus inhibiting their syntheses and purifications.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on bis(urea)-based tetraurea macrocycles have been reported and suggest that the bis(urea) unit may account for decent yield of the final ring-closure macrocyclization. [24][25][26] However, the principles underpinning the synthesis of bis(urea)-based macrocycles are still underdeveloped. To elucidate these, we first hypothesized that strong intramolecular hydrogen bonding of the bis(urea) unit can induce a well-defined, twisted conformation for macrocyclization.…”
Section: Introductionmentioning
confidence: 99%